Legacies of Paul de Man - Redfield, Marc, 1958- (Fordham University Press, 2007)
More than twenty years after his death, Paul de Man remains a haunting presence in the American academy. This work analyzes and evaluates aspects of de Man's powerful legacy. It focuses on: his great theme of 'reading'; his complex notions of 'history', 'materiality', and 'aesthetic ideology'; and his institutional role as a teacher.